2018
DOI: 10.1111/nph.15012
|View full text |Cite
|
Sign up to set email alerts
|

A novel experimental system using the liverwort Marchantia polymorpha and its fungal endophytes reveals diverse and context‐dependent effects

Abstract: Fungal symbioses are ubiquitous in plants, but their effects have mostly been studied in seed plants. This study aimed to assess the diversity of fungal endophyte effects in a bryophyte and identify factors contributing to the variability of outcomes in these interactions. Fungal endophyte cultures and axenic liverwort clones were isolated from wild populations of the liverwort, Marchantia polymorpha. These collections were combined in a gnotobiotic system to test the effects of fungal isolates on the growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 103 publications
1
43
0
Order By: Relevance
“…For example, a recent study by Nelson and colleagues [22] describes several growth-promoting endophytes associated with the liverwort Marchantia polymorpha , providing fertile ground for future Evo-MPMI research (see [23]). Other Marchantia species were shown to engage in mutualistic interactions with Glomeromycota [24,25].…”
Section: Fungal Symbioses Exemplify Ancient Plant-microbe Interactionsmentioning
confidence: 99%
“…For example, a recent study by Nelson and colleagues [22] describes several growth-promoting endophytes associated with the liverwort Marchantia polymorpha , providing fertile ground for future Evo-MPMI research (see [23]). Other Marchantia species were shown to engage in mutualistic interactions with Glomeromycota [24,25].…”
Section: Fungal Symbioses Exemplify Ancient Plant-microbe Interactionsmentioning
confidence: 99%
“…provide the Evo‐MPMI community with a unique resource that opens many avenues for future studies on both beneficial and detrimental plant–microbe interactions. On the beneficial side of the spectrum, Nelson et al . found that the most positive growth responses induced by species of the Colletotrichum and Nemania genera were modulated by nutrient availability, with stronger positive effects on plant growth in normal or high nutrient conditions compared to nutrient‐limiting conditions.…”
mentioning
confidence: 97%
“…In addition to the findings described in their article, Nelson et al . provide the Evo‐MPMI community with a unique resource that opens many avenues for future studies on both beneficial and detrimental plant–microbe interactions.…”
mentioning
confidence: 97%
See 2 more Smart Citations